(Aminomethylene)phosphonate Analogues as ZnII Chelators: Synthesis and Characterization. Issue 23 (20th June 2017) - Hevroni, Bosmat Levi; Jantz, Thomas; Gottlieb, Hugo E.; Fischer, Bilha
Abstract : A series of (aminomethylene)phosphonate (AMP) analogues, 8 –14, bearing one or two heterocyclic moieties (imidazolyl, pyridyl, and thiazolyl) on the aminomethylene group, were synthesized as potential Zn II chelators. The complexes of analogues8 –14 with Zn II ions were characterized by their stoichiometry, geometry, coordination sites, acid/base equilibria, and stability constants. Analogues8 –14 form stable water‐soluble 2:1 L/Zn II complexes, as established by Zn II titration, monitored by UV/Vis spectrophotometry and by 1 H and 31 P NMR spectroscopy. Acidity and stability constants were established for each derivative by potentiometric pH titrations. ML2 type Zn II complexes of AMP, bearing either an imidazolyl or pyridyl moiety, 8, 10, and12, exhibit high log β values (17.68, 16.92, and 16.65, respectively), while for the AMP‐thiazolyl (14 ) complex with Zn II, log β is 12.53. Generally, ligands9, 11, and13, bearing two heterocyclic moieties, present higher log β values (22.25, 21.00, and 18.28, respectively) vs. analogues bearing one heterocyclic moiety. Additionally, based on 1 H, 13 C, and 31 P NMR spectroscopic data, we propose a structure of the AMP‐(Im)2 ‐Zn II complex in solution, where the Zn II coordination sites involve the phosphonate moiety and both imidazolyl rings of the two binding molecules, forming an octahedral geometry around the Zn II ion. In summary, we propose a new family of water‐soluble high‐affinity Zn II chelators, in particular AMP‐(Im)2, which forms the most stable complex (log β 22). Abstract : A new family of water‐soluble, high‐affinity Zn II chelators was synthesized, based on an (aminomethylene)phosphonate (AMP) scaffold bearing one/two methylene heterocyclic moieties (imidazolyl/pyridyl/thiazolyl) on the aminomethylene group. The AMP analogue–Zn II complexes were characterized by their stoichiometry, geometry, coordination sites, acid/base equilibria, and stability constants.